Warming events projected to become more frequent and last longer across Antarctica ... - Feron, Sarah; Cordero, Raúl R.; Damiani, Alessandro; Malhotra, Avni; Seckmeyer, Gunther; Llanillo, Pedro ([London] : Macmillan Publishers Limited, part of Springer Nature, 2021)
Summer temperatures are often above freezing along the Antarctic coastline, which makes ice shelves and coastal snowpacks vulnerable to warming events (understood as periods of consecutive days with warmer than usual conditions). Here, we project changes in the frequency, duration and amplitude of summertime warming events expected until end of century according to two emission scenarios. By using both global and regional climate models, we found that these events are expected to be more frequent and last longer, continent-wide. By end of century, the number of warming events is projected to double in most of West Antarctica and to triple in the vast interior of East Antarctica, even under a moderate-emission scenario. We also found that the expected rise of warming events in coastal areas surrounding the continent will likely lead to enhanced surface melt, which may pose a risk for the future stability of several Antarctic ice shelves. ...